Relationship Between C-Reactive Protein-Albumin Ratio and Metastasis in Breast Cancer - Hazmi, Mohammad Zul; Panigoro, Sonar Soni; Yulian, Erwin Danil; Nugroho, Nyityasmono Tri; Agustina, Amilya (Indonesian Journal of Cancer, 2025)
Background: Breast cancer is a type of malignancy with the highest number of cases in the world and Indonesia. The C-reactive protein-albumin ratio (RCA) is a simple, feasible, and objective breast cancer serum marker representing inflammatory and nutritional status. There are not many studies regarding the relationship between RCA and breast cancer metastasis, especially in the advanced-stage case population in Indonesia.Method: Study with a cross-sectional design in 180 breast cancer patients stage III and IV at Cipto Mangunkusumo Hospital, who were diagnosed in 2018 until 2023. Comparative analysis of the RCA values between the groups with and without metastasis was carried out using the Chisquare test. All statistical test results are considered significant if the p-value is 0.05.Results: A receiver-operating characteristic curve (ROC) is a graphical analytical technique used to assess the effectiveness of a binary diagnostic classification method. The ROC area under the curve (AUC) value was 0.713 (IC 95%; 0.638–0.789) and significance 0.001, with the RCA cut-off value was 0.515 with sensitivity 74.4% and specificity 67.8%. The high RCA proportion was 53.3%. There is a significant relationship (p-value 0,001) between RCA level and the risk of metastasis in breast cancer patients. Liver and lung metastases of breast cancer are the most frequent locations. Conclusion: The CRP-albumin ratio has a significant relationship with the incidence of metastasis in breast cancer